Nanoscale Devices - Fundamentals and Applications - Gross, Rudolf; Sidorenko, Anatolie; Tagirov, Lenar (NATO Science Series II: Mathematics, Physics and Chemistry, Mathematics, Physics and Chemistry ;, 2006)
Over the last decade the interest in nanoscale materials and their applications in novel electronic devices have been increasing tremendously. This is caused by the unique properties of nanoscale materials and the outstanding performance of nanoscale devices. The fascinating and often unrivalled properties of nanoscale materials and devices opened new and sometimes unexpected fields of applications. Today, the widespread applications range from the detection of explosives, drugs and fissionable materials to bio- and infrared-sensors, spintronic devices, data storage media, magnetic read heads for computer hard disks, single-electron devices, microwave electronic devices, and many more. This book contains a collection of papers giving insight into the fundamentals and applications of nanoscale devices. The main focus is on the synthesis and characterization of nanoscale magnetic materials, the fundamental physics and materials aspects of solid-state nanostructures, the development of novel device concepts and design principles for nanoscale devices, as well as on applications in electronics with special emphasis on defence against the threat of terrorism.